Wireless information network - Pahlavan, Kaveh (Wiley series in telecommunications and signal processing., 1995)
"Because of a major "paradigm shift" in telecommunications, the world is rapidly moving away from nearly exclusive reliance on wired networks to an era of "tetherless" communications largely based on wireless technology. Evidence for the unprecedented growth of wireless communication can be found in the explosion of demand for paging and cellular telephone services, as well as the emerging plans for digital cellular